Gain Self-Calibration Procedure for Microphone Arrays - Tashev, Ivan (Proceedings of International Conference for Multimedia and Expo ICME 2004, 2004)
In many cases microphone arrays, used for beamforming or sound source localization, do not provide the estimated shape of the beam, noise suppression or localization precision. One of the reasons is the difference in the signal paths, caused by different sensitivity of the microphones and/or by the microphone preamplifiers. This paper presents simple and fast procedure for self-calibration of the microphone gains, suitable for real-time applications using microphone arrays for capturing audio signals. It is based on projection of sensor’s coordinates on direction of arrival line and approximation of received energy levels thus reducing the dimensions and speeding up the calculations. The proposed technique automatically calibrates the channels’ gains within ±0.45 dB when the manufacturing tolerance of the microphone sensitivity varies as much as ±4 dB. Tested in real environment.